Association of retinal vessel attenuation with visual function in eyes with retinitis pigmentosa - Nakagawa S (Dove Medical Press, 2014)
Satoko Nakagawa, Akio Oishi, Ken Ogino, Yukiko Makiyama, Masafumi Kurimoto, Nagahisa Yoshimura Department of Ophthalmology and Visual Sciences, Kyoto University Graduate School of Medicine, Kyoto, Japan Purpose: To investigate the association between visual changes and retinal vessel attenuation in patients with retinitis pigmentosa (RP).Design: A retrospective, longitudinal, observational cohort study.Methods: We analyzed 45 eyes from 45 subjects who were followed-up for ≥3 years at our clinic. Using the computer-based Interactive Vessel Analysis program, central retinal artery equivalent (CRAE) and central retinal vein equivalent (CRVE) were determined. Age- and sex-matched controls from normal subjects were selected from our archived fundus photograph library. Visual acuity, visual field area (Goldmann perimetry, V4e white test light), mean deviation (Humphrey perimetry, central 10-2 program), and central macular thickness (optical coherence tomography) were analyzed for correlations with CRAE and CRVE.Results: Both CRAE and CRVE were significantly decreased in RP eyes (94.9±13.5 µm and 155.6±20.0 µm, respectively) compared with control eyes (138.1±14.7 µm and 215.0±20.4 µm, respectively, both P<0.001). After 3 years of follow-up, visual field area was associated with both CRAE (r=0.584, P<0.01) and CRVE (r=0.500, P=0.008). A significant association was also observed between mean deviation and CRAE (r=0.298, P=0.047). In eyes with RP, a narrower vessel caliber at baseline was associated with a larger decline in visual acuity over the 3-year follow-up interval (CRAE: r=-0.344, P=0.021; CRVE: r=-0.314, P=0.035).Conclusion: Retinal vessel caliber is associated with some visual functions in patients with RP. Keywords: retinitis pigmentosa, retinal vascular caliber, central retinal artery equivalent, central retinal vein equivalent